Implementation Of The Project To Strengthen The Profile Of Pancasila Students (P5) In The Cupak Gerantang Musical Drama Performance At Smak Kesuma Mataram - Rizkika, Andhika; Purwati, Duwi; Agus Mega Saputra, Gde; Kurnia, Wahyu; Suryadmaja, Galih (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
The implementation of the Strengthening Pancasila Student Profile Project is carried out flexibly in terms of content, activities and implementation time. The Merdeka Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to deepen concepts and strengthen competencies. Teachers have the freedom to choose various teaching tools so that learning can be tailored to the learning needs and interests of students. This research is aimed at finding out the implementation and achievements made by teachers and students at SMAK Kesuma Mataram in carrying out a project to strengthen the profile of Pancasila students (P5) in the musical drama performance Cupak Gerantang. This research uses a case study approach with qualitative methods and quantitative methods, using questionnaires as research support. Based on the results of research on the application of P5 using musical drama performances as the output of P5 itself, it is indicated as a good process for instilling the values of the Pancasila student dimension for students in schools. The artistic process can be the right solution for schools to overcome the gap in the character of Pancasila students in the school environment. The collaboration between students could be said to be quite successful. It can be seen from how students can work together and be independent in the process they carry out. The process that students go through also invites them to be creative and think critically in dealing with problems in this project. So that the dimensions contained in P5 can be realized and well absorbed by SMAK Kesuma Mataram students.